Nuts and bolts of tropical tuna purse seine nets recycling: A circular business model - Andrés, Marga; Zudaire, Iker; Larreta, Joana; Asueta, Asier; González, Nekane; Molist, Marta; Uribesalgo, Edu; Basurko, Oihane C. (Frontiers in Sustainability, 2022)
Tropical tuna purse seiners are one of the most important contributors to End of Life (EoL) fishing gears in the world, and these fishing nets can become a promising secondary raw material. Thus, tuna companies are looking for possibilities to valorize them by applying circular economy. This contribution aims at assessing the viability of creating a circular business model out of recycled tropical tuna purse seine EoL nets. The yearly contribution of Spanish Tuna Freezer purse seine companies to EoL fishing nets was estimated at 900 tonnes. Three pilot projects were implemented (involving 80 tonnes of EoL tuna nets) to learn about the monetary and material flows, supply chain, stakeholders’ perception, and the environmental impacts of upcycling polyamide nets into four marketable products (i.e., conditioned fishing nets, backpacks, fishers’ dungarees, and sunglasses). Results indicate that recycled regrinds/flakes and pellets were 37% and 50% respectively more expensive than virgin counterparts, but the yarn may achieve competitive production costs in the textile industry, with an additional environmental benefit close to 69% per kg of virgin-origin yarn. The challenges faced when recycling EoL polyamide fishing nets were discussed. Innovation and logistics appear to play a fundamental role on making the business sustainable. Besides, the circular business model methodology to assess the value proposition was also discussed on its empirical application.